Analysis of Organizational Culture and Employee Loyalty at Bank Sumedang - Sukmayadi Sukmayadi; Destiany Ramadhyanti (SINTESA, 2023)
The background of this study is that there are indications of anorganization at Sumedang Bank that has been running quite well but needsto be optimized. This study aims to apply organizational culture knowledgeand determine the application of organizational culture and determineemployee loyalty at Sumedang Bank. This research uses qualitativeresearch methods with data collection techniques, namely interviewobservation and documentation. The informants in this study weredetermined using the purposive sampling method, namely a total of 6people. The final results of this study concluded that the cultureorganizational owned by Bank Sumedang had been going well but was stillnot optimal in the way it behaved, dress, and so on. While employees atBank Sumedang have been running well but not optimally. This can beseen from several things, namely there are several bank employeesbecause they are late for work from the specified hours. Therefore, theresults of this study can be used as references and recommendations tosupport the smooth running of Organizational Cultute and EmployeeLoyalty at Bank Sumedang